2013
DOI: 10.1002/hup.2340
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic polymorphisms and response to escitalopram and venlafaxine over 8 weeks in major depression

Abstract: Ethnicity may have differential effects on the 5-HTTLPR genotype-efficacy relationship. Results suggest that l/l allele for 5-HTTLPR is associated with a robust treatment response to ESC in Caucasian subjects only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 20 publications
3
15
0
2
Order By: Relevance
“…HTTLPR S/S genotype carriers had a reduced antidepressant effect compared to those carrying the L allele. This finding is consistent with our previous work showing that L/L allele for HTTLPR is associated with a robust treatment response to escitalopram in Caucasian subjects [10]. However this was in contrast to the finding by Proft et al [4], which showed a significant association between SLC6A4 genotype (l A l A ) and poor response to venlafaxine.…”
supporting
confidence: 92%
“…HTTLPR S/S genotype carriers had a reduced antidepressant effect compared to those carrying the L allele. This finding is consistent with our previous work showing that L/L allele for HTTLPR is associated with a robust treatment response to escitalopram in Caucasian subjects [10]. However this was in contrast to the finding by Proft et al [4], which showed a significant association between SLC6A4 genotype (l A l A ) and poor response to venlafaxine.…”
supporting
confidence: 92%
“…However, the study focused on sertraline metabolism in relation to CYP2C19, failed to identify any significant changes [44]. Furthermore, the same 8 weeks' study previously described for CYP2D6, found contrasting differences between CYP2C19 poor/intermediate and CYP2C19 extensive/ultra-rapid metabolizer after administration of escitalopram and venlafaxine [39].…”
Section: Cyp2d6mentioning
confidence: 93%
“…A metaanalysis suggested that the long allele of 5-HTTLPR may be a predictor of antidepressant response in Caucasians, but not Asians [54]. Two recent studies also showed that the l/l allele for 5-HTTLPR was associated with a better treatment response to escitalopram, but in Caucasians only [55,56]. In some Asian studies, favorable treatment outcome was associated with the short allele [57,58].…”
Section: The Serotonin Transporter Gene-linked Polymorphic Regionmentioning
confidence: 95%